The pro alpha 2(V) collagen gene is evolutionarily related to the major fibrillar-forming collagens. - Weil, D (1987)
A number of overlapping cDNA clones, covering 5.2 kb of sequences which code for the human pro alpha 2(V) collagen chain, have been isolated. Analysis of the structural data have indicated a close evolutionary kinship between the pro alpha 2(V) chain and the major fibrillar collagen types. Isolation and analysis of an 8 kb genomic fragment has further supported this notion by revealing a homologous arrangement of nine triple-helical domain exons. These studies have therefore provided conclusive evidence which categorizes the Type V collagen as a member of the Group 1 molecules, or fibrillar-forming collagens.